(untitled) (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2021)
The article deals with the problem of optimal motion control of a two-machine system. The problems of stabilization and control of a two-machine system are described by nonlinear differential equations. These mathematical models describe the processes in complex systems consisting of many turbines and generators, and are used to analyze them. The relevance of these models lies in the fact that they allow you to model various pre-emergency, emergency and post-emergency situations. The stability of the synthesized system is checked by the Lyapunov function method. The correctness of the solutions found is verified by the numerical solution of the considered and given example. The controllability of the model under consideration is determined by the study of the global asymptotic stability of dynamical systems in cylindrical phase systems. The results obtained are demonstrated by a numerical example.